2016
DOI: 10.1016/j.japh.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of medication reviews by community pharmacists

Abstract: Objectives: Many Canadians use prescription medicines that are unnecessary or that can lead to adverse events. In response, many provinces have introduced programs in which pharmacists are paid to perform medication reviews with patients. As the evidence on such programs is equivocal, we investigated the impact of British Columbia's program. Design: Interrupted time series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 27 publications
(32 reference statements)
0
36
0
1
Order By: Relevance
“…A similar finding was seen in another study, where medicines were issued for old prescriptions for months. 7 In this study it was found that the number of community pharmacists provided alert to the public about the ill effects of drugs was 79% and 69% respectively in and around Coimbatore. There was a study expressing that only 40-50% community pharmacists provide alert the public about the ill effects of drugs.…”
Section: Discussionmentioning
confidence: 73%
“…A similar finding was seen in another study, where medicines were issued for old prescriptions for months. 7 In this study it was found that the number of community pharmacists provided alert to the public about the ill effects of drugs was 79% and 69% respectively in and around Coimbatore. There was a study expressing that only 40-50% community pharmacists provide alert the public about the ill effects of drugs.…”
Section: Discussionmentioning
confidence: 73%
“…Text and other data analytics tools enabled data to be brought together and interpreted from a number of sources, and shortcomings in data formats and documentation to be, to an extent, circumvented. The full analysis will facilitate a more tailored approach [24] relatable to groups of patients or combinations of morbidities, to help support the decision-making process of which drugs can be usefully deprescribed -there is evidence that patients want to reduce their medication [19], [45], however previous attempts to reduce the numbers of inappropriate prescriptions have failed [25].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that pharmacists often consider an expanding scope of practice to be a "legitimization" of prior practices and are more likely to offer a new service if they were already doing it in a less formal manner, although there can be a tension between a more professional role and the day-to-day need for technical efficiency [2][3][4][5]. The challenge, however, is that new services associated with an expanding scope can have low uptake, may be delivered in ways that do not align with policy, or may be preferentially offered to less complicated patients [6][7][8][9]. While current methods of continuing professional development commonly used in Canada, such as conference attendance and home study units, are still deemed valuable, they may be insufficient to facilitate widespread practice change [10].…”
Section: Introductionmentioning
confidence: 99%